The right drugs at the right time for the right patient: the MD Anderson precision oncology decision support platform. Issue 12 (December 2015) - Johnson, Amber; Zeng, Jia; Bailey, Ann M.; Holla, Vijaykumar; Litzenburger, Beate; Lara-Guerra, Humberto; Mills, Gordon B.; Mendelsohn, John; Shaw, Kenna R.; Meric-Bernstam, Funda
Highlights: Precision oncology matches tumor molecular alterations with appropriate therapies. Decision support platforms are crucial for optimal and scalable implementation. Actionability of specific variants, as well as specific genes, should be assessed. Level of evidence should be considered for each alteration and therapy considered. Clinical outcome registries for drugs used in experimental settings are suggested. Abstract : The development of resources for clinical interpretation of cancer-associated genetic alterations has significantly lagged behind the technical developments enabling their detection in a time- and cost-efficient manner. The lack of scientific and informatics decision support for oncologists can lead to no action being taken or suboptimal therapeutic choices being made, which could affect the clinical outcome of a patient as well as convoluting research findings from clinical trials. In this article, we describe the precision oncology decision support (PODS) platform developed within The Sheikh Khalifa Bin Zayed Al Nahyan Institute for Personalized Cancer Therapy (IPCT) at MD Anderson Cancer Center; the platform aims to bridge the gap between molecular alteration detection and identification of appropriate treatments.